Simulated time trial using three different pedal rate protocols - Loveday, D. E.; Coast, J. R. (International Journal of Performance Analysis in Sport, 2010)
We sought to determine whether pedaling strategy during a 30 minute simulated time trial affected caloric requirements. The simulation consisted of a 30 minute bout divided into three successive 10 minute workloads (250W, 200W and 300W) ridden with three different cadence protocols. Protocol 1 matched the cadence to the power output of each 10 minute period, protocol 2 matched cadence to the average power output over bout and protocol 3 used a constant 95 rpm (common cadence in competition). Heart rate (HR), oxygen consumption (VO2), and perceived exertion (RPE) were measured. The average total Kcal requirement for each protocol (1-3) was 470.1, 469.8 and 494.3, respectively. The average HR for each protocol was 151.5, 149.3 and 153.0 and the average RPE for each protocol was 12.8, 12.3 and 12.4. Protocol 3 required the greatest amount of energy (P<0.001) and elicited a higher HR (P<0.05) when compared to protocols 1 and 2. At the same time, RPE was not different across bouts (P>0.05). The results show energy expenditure was significantly elevated during the constant 95 rpm bout and that perceived exertion was not an accurate indicator of energy expenditure.